2017
DOI: 10.1021/acs.molpharmaceut.7b00325
|View full text |Cite
|
Sign up to set email alerts
|

Multiresponsive Nanogels for Targeted Anticancer Drug Delivery

Abstract: Nanogels with a biomolecular coating (biocoating) were shown to be capable of triggered delivery of anticancer drug Doxorubicin. The biocoating was formed utilizing binding between glycogen and the tetra-functional lectin Concanavalin A, which can be triggered to disassemble (and release) upon exposure to glucose and changes in solution pH. We also show the nanogel's thermoresponsivity can be used to accelerate Doxorubicin release. Moreover, we showed that transferrin immobilized on the nanogel surface could a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(27 citation statements)
references
References 41 publications
0
27
0
Order By: Relevance
“…Moreover, their high water content and living tissue-like physical properties ensure high biocompatibility. Nanogels meant as anticancer drug delivery systems have been recently designed [52,53].…”
Section: Polymeric Nanoparticlesmentioning
confidence: 99%
“…Moreover, their high water content and living tissue-like physical properties ensure high biocompatibility. Nanogels meant as anticancer drug delivery systems have been recently designed [52,53].…”
Section: Polymeric Nanoparticlesmentioning
confidence: 99%
“…Thermosensitive [ 61 ], pH-sensitive [ 62 , 63 ], glucose-sensitive [ 64 ], redox-sensitive [ 65 ], and magnetic-field-sensitive [ 66 ] nanogels are applicable to the treatment of many diseases ( Figure 3 ). Furthermore, nanogels can be tailored as dual or multi-responsive structures [ 42 , 67 ]. Deng et al explored the synthesis and properties of poly (N,N-dimethyl aminoethyl methacrylate -g- Ethylene glycol) P(DMAEMA-g-EG) nanogel carriers with 190–600 nm diameters, which showed pH, ionic strength and temperature sensitivity with LCSTs of about 35 °C [ 68 ].…”
Section: Nanogelsmentioning
confidence: 99%
“…Stimuli-responsive nanocarriers have the potential to induce enhanced permeability [ 40 , 41 ]. In addition, targeted delivery enables selective delivery of the drug to the diseased tissue while leaving the healthy tissue unharmed [ 42 ]. Despite the numerous advantages of nanocarriers for drug delivery, there are some challenges to be tackled, including difficulty of synthesis, low stability, and the circulation time of nanocarriers in blood circulation.…”
Section: Introductionmentioning
confidence: 99%
“…Zhang et al developed transferrin immobilized PNIPAM‐based microgels for targeted delivery of DOX . The surface of nanogels was coated using glycogen and the tetrafunctional lectin Concanavalin A which can disassemble in the presence of glucose and variation in pH.…”
Section: Microgels For Drug Delivery Applicationmentioning
confidence: 99%
“…[157] Zhang et al developed transferrin immobilized PNIPAMbased microgels for targeted delivery of DOX. [158] The surface of nanogels was coated using glycogen and the tetrafunctional lectin Concanavalin A which can disassemble in the presence of glucose and variation in pH. The experiments with HepG2 cells showed that tranferrin played an important role in accelerating the nanogel uptake by cancer cells as compared to the nanogels without transferrin.…”
Section: Passive and Active Targeting For Drug Releasementioning
confidence: 99%